Imperfect competition, real estate prices and new stylized facts - Ronald Ravinesh Kumar; Peter Stauvermann (Journal of Risk and Financial Management, 2022)
In this paper, we develop an overlapping generation model with imperfect competition and land to provide a theoretical foundation for some empirical observations made since the end of the 1970s. The problem is that these new 'stylized facts' do not coincide with Kaldor's stylized facts and unfortunately the standard growth models are not able to explain these new facts. By using our model, we are able to theoretically derive these new facts and to provide a theoretical foundation for them. In particular, increasing market concentration leads to a decline in the labor income share, to a decline in the capital income share, to a decline in the natural interest rate, to an increasing wealth to income ratio, and to an over-proportional increase in land prices in developed countries. The model developed for analysis has close similarity with the standard neoclassical overlapping generation model with endogenous growth and land. The main difference between the standard neoclassical and the model in this paper is the market structure. Instead of assuming perfectly competitive markets, we assume an oligopolistic market structure. This leads to the occurrence of pure profits for firms and, accordingly, the input factors are no longer paid their marginal products.
Keywords: 330; imperfect competition; oligopoly; endogenous growth; land; overlapping generations